2010
DOI: 10.1126/science.1192606
|View full text |Cite
|
Sign up to set email alerts
|

The Chlorine Isotope Composition of the Moon and Implications for an Anhydrous Mantle

Abstract: Arguably, the most striking geochemical distinction between Earth and the Moon has been the virtual lack of water (hydrogen) in the latter. This conclusion was recently challenged on the basis of geochemical data from lunar materials that suggest that the Moon's water content might be far higher than previously believed. We measured the chlorine isotope composition of Apollo basalts and glasses and found that the range of isotopic values [from -1 to +24 per mil (per thousand) versus standard mean ocean chlorid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
203
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(218 citation statements)
references
References 26 publications
15
203
0
Order By: Relevance
“…In particular, direct measurements of water in incompletely degassed, primitive lunar glasses made in several laboratories have shown that water concentrations are similar to those observed in magmas from Earth's depleted upper mantle (Saal et al 2008;Chen et al 2015;Hauri et al 2015;Wetzel et al 2015) and that the isotopic composition of this water is approximately chondritic (Friedman et al 1974;Saal et al 2013;Barnes et al 2014;Füri et al 2014;Tartèse et al 2014). Although these results and their generality to the Moon as a whole are not universally accepted (Sharp et al 2010;Greenwood et al 2011;Albarède et al 2015), these observations have been interpreted as signifying a common origin for terrestrial and lunar water ). The incorporation of water into the Moon in concentrations similar to those of the Earth is seemingly at odds with the widely held view of the origin of the Moon as the result of an impact between the early Earth and a Mars-sized impactor (e.g., Canup and Asphaug 2001;Pahlevan and Stevenson 2007).…”
Section: Introductionmentioning
confidence: 95%
“…In particular, direct measurements of water in incompletely degassed, primitive lunar glasses made in several laboratories have shown that water concentrations are similar to those observed in magmas from Earth's depleted upper mantle (Saal et al 2008;Chen et al 2015;Hauri et al 2015;Wetzel et al 2015) and that the isotopic composition of this water is approximately chondritic (Friedman et al 1974;Saal et al 2013;Barnes et al 2014;Füri et al 2014;Tartèse et al 2014). Although these results and their generality to the Moon as a whole are not universally accepted (Sharp et al 2010;Greenwood et al 2011;Albarède et al 2015), these observations have been interpreted as signifying a common origin for terrestrial and lunar water ). The incorporation of water into the Moon in concentrations similar to those of the Earth is seemingly at odds with the widely held view of the origin of the Moon as the result of an impact between the early Earth and a Mars-sized impactor (e.g., Canup and Asphaug 2001;Pahlevan and Stevenson 2007).…”
Section: Introductionmentioning
confidence: 95%
“…Chlorine isotopes have been strongly fractionated in some lunar materials (−1 to +24 ), leading Sharp et al [32] to suggest a mechanism of volatilization of Cl as metal halides (e.g. NaCl, ZnCl 2 , FeCl 2 ), loss of Cl during basalt eruption on the lunar surface and, consequently, an essentially anhydrous lunar interior.…”
Section: (B) Chlorinementioning
confidence: 99%
“…where X is the heavier mass isotope ( 34 S, 37 Cl, 41 K, 66 Zn) and Y is the lighter mass isotope ( 32 S, 35 Cl, 39 [53,54,56], for (b) from [32,[57][58][59], for (c) from [31] and for (d) from [34,37].…”
Section: Isotopic Fractionation Of Moderately Volatile Elements In Comentioning
confidence: 99%
See 1 more Smart Citation
“…Of the Apollo 12 basalt suite, 12040 is considered one of the slowestcooled samples 21 , suggesting the magma of 12040 may have underwent extensive degassing of water. Significant degassing of water has recently been suggested for 12040 based on Cl isotope composition of apatite 22 . Apatite grain fragments in the late-stage matrix regions of breccia samples 12013 and 14305,94 were also found to have very low water.…”
mentioning
confidence: 99%